Effect of Different Intensity Exercise on Intestinal Microbiota - ÖZKAN, Ali; DEMİRHAN, Bilal and genç, Ayça and AYDIN, Recep and ERKILIÇ, Ali Ozan and GÜDER, Ferhat and MÜLHİM, Mustafa Alper (Progress in Nutrition, 2021)
Aim: The aim of this study is to investigate the effect of different intensity exercise on the intestinal microbiota. Material and Method: Professional footballers (n = 5), amateur footballers (n = 5) and sedentary ones (n = 5), a total of 15 volunteer men whose age were between 18-24 participated in the study. In order to determine the Pielou’s Evenness Index of all groups, metagenomics analysis was performed using the Next Generation Sequencing method with Illumina MiSeq analyzer by taking stool sample for once. In addition, Food frequency questionnaire was applied to determine participants’ eating habits. SPSS 20.0 and Minitab 17 package programs were used in statistical analysis, and the significance level was taken as p <0.05.Results: In this study, while it was found that amateur footballers (AF) had the most evenness quantitative distribution of types (the difference of Pielou_e was very low 0.01), sedentary ones had the least (Pielou_e has the lowest value of 0.69 - 0.73). In addition, it has been determined that the groups have different eating habits. Conclusion: Exercise type, intensity and nutrition have an important role in shaping the intestinal microbiota. It can be said that regular exercise with medium intensity has positive effects on evenness index of intestinal microbiota compared to high intensity exercise and sedentary lifestyle. In addition, we think that the participants’ eating habits affect the evenness index, too.